Effects of fetal exposure to drugs: systematic review - Bankes, Julia, author (Colorado State University. Libraries, 2024)
This paper explores the long-term effects of fetal drug exposure on individuals, examining the implications for cognitive, physical, and social development. This paper reviews existing literature to consolidate an understanding of the effects of in-utero drug exposure. Prenatal exposure to substances such as opioids, alcohol, tobacco, and illicit drugs adversely affects neurodevelopment creating cognitive challenges and behavioral disorders. The paper also discusses the stages of fetal development, the types of substances commonly involved, and the physiological mechanisms by which these drugs impact fetal growth. The findings underscore the importance of informed interventions and holistic treatment approaches for mothers and infants affected by drug exposure, aiming to enhance developmental outcomes and reduce societal stigma. This paper ultimately calls for further research into effective care strategies and the development of supportive frameworks for affected families.
Colorado State University. Honors.
Keywords: Neonatal Abstinence Syndrome; drug withdraw; fetal development